2009
DOI: 10.1359/jbmr.081002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced COX-2 Expression in Aged Mice Is Associated With Impaired Fracture Healing

Abstract: The cellular and molecular events responsible for reduced fracture healing with aging are unknown. Cyclooxygenase 2 (COX-2), the inducible regulator of prostaglandin E2 (PGE2) synthesis, is critical for normal bone repair. A femoral fracture repair model was used in mice at either 7–9 or 52–56 wk of age, and healing was evaluated by imaging, histology, and gene expression studies. Aging was associated with a decreased rate of chondrogenesis, decreased bone formation, reduced callus vascularization, delayed rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
121
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 69 publications
5
121
0
Order By: Relevance
“…Naik et al (2009) mentioned that expression of COX-2 during the early inflammatory phase of repair regulates chondrogenesis, bone formation, and remodeling. Huang et al (2014) reported that COX-2-deficient periosteal progenitors present impaired osteogenic and chondrogenic differentiation in cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Naik et al (2009) mentioned that expression of COX-2 during the early inflammatory phase of repair regulates chondrogenesis, bone formation, and remodeling. Huang et al (2014) reported that COX-2-deficient periosteal progenitors present impaired osteogenic and chondrogenic differentiation in cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The initial fracture hematoma develops immediately after injury and contains various immune cell populations originating from bone marrow, disrupted blood and lymph vessels. 8,17 So far, studies on the early inflammatory phase of fracture healing primarily focused on the infiltration of immune cells into already existing fracture hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…However, the participation of immune cells and soluble factors derived from them are hypothesized to be decisive for tissue repair like wound healing or bone regeneration. [5][6][7][8] Macrophages are critical for the clearance of cell debris and for matrix degradation during tissue regeneration 9 and neutrophil recruitment is important in regard to fighting infections 10 which are more likely to occur in damaged tissues. Depletion of macrophages and the depletion of all T lymphocytes lead to less effective wound healing, while the depletion of CD8 1 T cells exhibits the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, hypoxia exerts a significant influence (Heppenstall et al, 1976), via regulating the expression of transcriptional factors and cytokines (Warren et al, 2001) such as hypoxia-inducible factors (Akeno et al, 2001), vascular endothelial growth factor (Bouletreau et al, 2002) and bone morphogenetic protein 2 (BMP-2) (Bouletreau et al, 2002). And such factors/cytokines then pose regulatory roles on the wound healing or bone regeneration (Naik et al, 2009;Kolar et al, 2010). BMPs, such as BMP-2 (Hu et al, 2013;Gao et al, 2015), alkaline phosphatase (ALP) (Huang et al, 2015), osteopontin (Jiang et al, 2015) and osteocalcin (Huang et al, 2015), have been indicated to be deregulated by hypoxia in the differentiation of MSCs during bone repair.…”
Section: Introductionmentioning
confidence: 99%